SIMPLE, RAPID, ECONOMICAL AND HIGH YIELDING METHOD FOR EXTRACTING GENOMIC DNA FROM COTTON (GOSSYPIUM SPP.) - GULAMNABI L.VANTI; ISHWARAPPA S. KATAGERI; BALE M. SWAMY; VAMADEVAIAH HIREMATH (International Journal of Pharma and Bio Sciences, 2016)
The complex allotetraploid nature of the cotton genome makes genetic, genomic and functional analyses extremely challenging. Until now, several methods have been published for the purpose, but none is found to be universally applicable. To overcome these difficulties, we have designed a protocol for the isolation of high quality and quantity genomic DNA from young as well as older leaves, which is suitable for molecular biology applications. We modified and optimized the Cetyltrimethylammonium bromide (CTAB) method for plant genomic DNA extraction in large quantity and described protocol takes less than 80 min and does not require RNase treatment and purification steps. The DNA yield ranged between 700–800 µg per gram of leaf tissue. Quantification of isolated DNA from spectral (A260/A280) measurements as well as agarose gel electrophoresis showed negligible polysaccharide and protein contamination. Thus the extracted DNA was very much suitable for southern hybridization and PCR based molecular studies.